MORPHOMETRIC ANALYSIS OF DUHOK WATERSHED - Ghariba Y. H.; J. I. Salim; H. S. Mohammad Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to obtain morphometric parameters of Duhok watershed evaluated through three aspects. The area was located at Duhok governorate with covers 394.87Km2. Depending on stream orders, ten of sub-watersheds were extracted from the main watershed. Furthermore, Duhok watershed stream orders ranged from 1 to 6, as well as the total number of segmented stream reported for the total number of orders was (4175). The results of the current study indicate the Duhok watershed has a high relief ratio (0.026 m/km) and relative relief (0.95) which refers to steep slopes and excessive runoff. The ruggedness value is (4.09) indicates the study region is rugged with high density of streams also the low value of hypsometric integral (0.37) indicates the mature stage of watershed age. However, the watershed’s flatter flow regime and elongated shape are confirmed by the values of form factor (0.23), elongation ratio (0.54), and circulation ratio (0.40). The watershed mean bifurcation ratio is 4.13, indicating significant structural disruption, while the value of stream frequency (10.69 streams/km2) suggests dense surface runoff and steeper topography. a very fine drainage texture (37.66) which leads to a higher risk of erosion. The findings of this study will be valuable in watershed management, water resources and protecting the environment in the future.